A case of prenatal isolated talipes and 22q11.2 deletion syndrome—an important chromosomal disorder missed by noninvasive prenatal screening. (13th March 2018) - Cheung, Ka Wang; Lai, Carman Wing Sze; Mak, Christopher Chun Yu; Hui, Pui Wah; Chung, Brian Hon Yin; Kan, Anita Sik Yau
Abstract : What's already known about this topic? NIPS is commonly used to screen for chromosomal abnormality. The test can be extended to screen for microdeletions such as 22q11.2 deletion syndrome. What does this study add? We present a case of 22q11.2 deletion syndrome missed by NIPS in a fetus with isolated bilateral talipes. Clinicians should be aware of the controversy surrounding the use of NIPS for 22q11.2 deletion syndrome and that a negative test does not exclude the diagnosis.